2018
DOI: 10.21474/ijar01/6684
|View full text |Cite
|
Sign up to set email alerts
|

Lead (Pb) Contamination in Street Vendors Fried Foods in School Area of Padang Municipality, Indonesia.

Abstract: This study aimed to analyze the effect of transportation on lead (Pb) concentration in fried street foods of Padang school area and to analyze hygiene and sanitation handling against processed fried street foods ingredients. Samplings for the analysis of Pb concentration in fried street foods of school was conducted at the school area that located on the primary arterial road and the local secondary road in Simpang Haru District. Fried street food sampling and vehicle volume counting were conducted for 7 conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 1 publication
0
3
0
3
Order By: Relevance
“…Menurut Ihsan, dkk, posisi berdagang di tepi jalan raya memungkinkan penyerapan logam berat dari asap kendaraan bermotor, seperti timbal (Pb). 13 Hasil pembakaran ini, berasal dari senyawa tertrametil-Pb dan tetraetil-Pb yang ditambahkan dalam bahan bakar kendaraan bermotor dan berfungsi sebagai anti ketuk (anti-knock) pada mesinmesin kendaraan. Senyawa ini dapat larut dalam minyak dan air.…”
Section: Pendahuluanunclassified
See 2 more Smart Citations
“…Menurut Ihsan, dkk, posisi berdagang di tepi jalan raya memungkinkan penyerapan logam berat dari asap kendaraan bermotor, seperti timbal (Pb). 13 Hasil pembakaran ini, berasal dari senyawa tertrametil-Pb dan tetraetil-Pb yang ditambahkan dalam bahan bakar kendaraan bermotor dan berfungsi sebagai anti ketuk (anti-knock) pada mesinmesin kendaraan. Senyawa ini dapat larut dalam minyak dan air.…”
Section: Pendahuluanunclassified
“…Penelitian Ihsan, dkk pada jajanan gorengan di area sekolah Kota Padang, menunjukkan rata-rata kandungan timbal (Pb) dari makanan gorengan jalanan pada jalan arteri primer berkisar antara 0,249-0,288 ppm dan di jalan lokal sekunder berkisar antara 0,155-0,218 ppm. 13 Kemudian dalam penelitian Tuloly pada jajanan gorengan di lingkungan workshop Universitas Hasanudin Makassar, diketahui bahwa sampel pisang goreng mengandung timbal berkisar antara 0,65 ppm -3,86 ppm. Sedangkan untuk tahu isi kandungan timbalnya berkisar antara 0,93 ppm -3,68 ppm.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Then the condition of the merchandise is opened without a cover (26). The study on the lead contamination of fried food in 2018 street vendors showed that the average Pb content of fried food on the primary arterial road was greater than the fried food on the secondary local road (5).…”
Section: Correlation Of Sanitation Conditions Of the Seller With The mentioning
confidence: 99%
“…The high exposure to pollutants can affect the lead content of fried foods, researchers who perform measurements show that the average Pb content of fried foods on the primary arterial road is greater than the fried foods on the local secondary road namely 0.2672 ppm and 0.2791 ppm. While the lead rate of fried foods on the local secondary road is 0.1851 ppm and 0.1911 ppm (5).…”
Section: Introductionmentioning
confidence: 95%